The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1590/1980-5373-mr-2017-1103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pile Orientation on the Shear Strength of Stitched Foam Sandwich Panel

Abstract: Stitched foam sandwich panel is a newly developed sandwich structure used in various structural applications. The sandwich skins are made of glass-fiber/epoxy-matrix composite; their interior layers are connected with glass yarn called piles. This paper investigates the effect of pile orientation on the shear strength of stitched foam sandwich panel. Four types of pile orientation are used; 90º, 45º, 90 º/45 º and 90º/45º/90º.The results are compared with a non-stitched sandwich panel. From the results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For example, Han 18 analysed the effects of the impact energy and stitch density on low-velocity impact damage to stitched foam sandwich composites through experiments and numerical studies. Lascoup B 19 and Ramraj 20 studied the effects of the stitch angle on the shear properties of foam sandwich composites. The study of a single stitch thread could reveal the bridging force and fracture mode of the stitched foam sandwich composites.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Han 18 analysed the effects of the impact energy and stitch density on low-velocity impact damage to stitched foam sandwich composites through experiments and numerical studies. Lascoup B 19 and Ramraj 20 studied the effects of the stitch angle on the shear properties of foam sandwich composites. The study of a single stitch thread could reveal the bridging force and fracture mode of the stitched foam sandwich composites.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that stitched core increased the ultimate shear strength and shear modulus of the sandwiches. 34 Foam-filled corrugated cores, i.e. steel facings/Al foam–steel core webs, 35 and glass/epoxy facings/PVC foam core-glass/epoxy core webs, 36 in the form of rectangular, trapezoidal and triangular also contributed to improving bending load capacities and flexural stiffness of the structure.…”
Section: Introductionmentioning
confidence: 99%